Analysis of target radar cross section (RCS) using computer simulation technology (CST) software / Mohd Azlan Afipudin - Afipudin, Mohd Azlan (2013)
This paper describes about the design and analysis target radar cross-sectional (RCS) for radar system topology using Computer Simulation Technology (CST MWS) Software. Simulation of the target radar is done in order to demonstrate the radar cross sectional and farfield simulation. The result consists of comparison between target radar cross-sectional for different selected targets angle position and specific frequency of a same car, and RCS for different cars model. The simulation process was done using transient solver from the software application. This simulation process will be the input of the prediction of the performance of forward scatter radar (FSR).